2014
DOI: 10.1371/journal.pone.0093267
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of μ-Conotoxin PIIIA Binding to the Voltage-Gated Na+ Channel NaV1.4

Abstract: Several subtypes of voltage-gated Na+ (NaV) channels are important targets for pain management. μ-Conotoxins isolated from venoms of cone snails are potent and specific blockers of different NaV channel isoforms. The inhibitory effect of μ-conotoxins on NaV channels has been examined extensively, but the mechanism of toxin specificity has not been understood in detail. Here the known structure of μ-conotoxin PIIIA and a model of the skeletal muscle channel NaV1.4 are used to elucidate elements that contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 65 publications
3
38
0
Order By: Relevance
“…As discussed above for GIIIA, R20 makes contact with the outer D762 residue, and the EEDD ring is not wide enough to accommodate a second arginine on top of R14 and K17, which have established contacts with the EEDD ring. The Na V 1.4-PIIIA complex was also modeled in [ 27 ], where two binding modes with similar binding free energies were proposed. The first involving K9 and R12 is supported neither by the experimental data ( Table 1 ) nor by the arguments based on alignment with GIIIA, which has the best characterized binding mode experimentally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above for GIIIA, R20 makes contact with the outer D762 residue, and the EEDD ring is not wide enough to accommodate a second arginine on top of R14 and K17, which have established contacts with the EEDD ring. The Na V 1.4-PIIIA complex was also modeled in [ 27 ], where two binding modes with similar binding free energies were proposed. The first involving K9 and R12 is supported neither by the experimental data ( Table 1 ) nor by the arguments based on alignment with GIIIA, which has the best characterized binding mode experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, initial efforts have focused on modeling of Na V 1.4 channel, as a great deal of functional data is available for this channel. These studies include binding of tetrodotoxin [ 25 , 26 ] and µ -conotoxins [ 27 , 28 , 29 ] to the Na V 1.4 channel.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study has also been performed for binding of μ-conotoxin PIIIA to Na V 1.4 [81], where two distinct binding modes with very similar binding free energies have been found. This situation is very different from toxin binding to potassium channels where the pore-inserting lysine ensures a unique binding mode and a complete blocking of the narrow selectivity filter.…”
Section: Sodium Channel Toxinsmentioning
confidence: 80%
“…Thus, one can use the channel-blocking capacity of a toxin to distinguish among the predicted binding modes. Unfortunately, there are limited functional data on binding of μ-PIIIA [82,83], so it is difficult to check the validity of the complex structure and the Na V 1.4 model used in [81]. The possibility of multiple binding modes with similar binding free energies needs to be investigated further using the Na V 1.4 model that has already been validated with the μ-GIIIA data [12].…”
Section: Sodium Channel Toxinsmentioning
confidence: 99%
“…However, both experimental and theoretical studies have suggested that these assumptions are invalid in certain systems. For example, a single mutation can induce significant structural changes to a toxin [ 41 , 42 , 43 ] and multiple binding modes of similar energetics are required to describe the action of certain toxins [ 44 , 45 , 46 ]. Therefore, experimental data can be difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%